Pembelajaran Bahasa Jawa Krama Untuk Menumbuhkan Sikap Sopan Santun Anak - Anggun; Khoirun Nisak; Siti Nihar Salsabilah; Suci Ahirotunisa; Fatkhurrohman (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Javanese is a language commonly used in Javanese ethnic communities. Javanese is one of the regional languages ​​used in daily life by Javanese people for communication between people. Manners are not something that can be learned quickly. Etiquette takes a long time to master, especially when it comes to children's language literacy. Developing language politeness must start from an early age. The emphasis on teaching children is necessary to teach children the norms of politeness of their native culture. Local wisdom is considered to have great value because it is an idea that lives in people's minds and its values ​​are also used as a guide in actions, words and deeds. This research uses a qualitative approach with descriptive research type and aims to find out whether learning Javanese at school can foster a sense of politeness in children from an early age. This research uses observation and interview methods. The results of this research are that children learn Javanese which can improve their manners. In this research, some children already have the manners that we want to examine, but there are also children whose manners have not yet developed. Children's learning about politeness is not only obtained through school, but parents also contribute to the growth of politeness values. From the results of this research, it is hoped that teachers and parents can provide more learning to children regarding politeness norms.